Correligionarias. Women in the Republican Mobilization at the Beginning of Spanish Restoration Regime (1875-1900) - Anchorena Morales, Oscar (Hispania Nova, 2025)
Since the last military pronunciamiento of 1874 brought in the regime of the Restoration, a restrictive framework for citizen participation under a form of adulterated liberalism took shape in Spain. Among the main victims of the new institutional architecture were the republican forces, the preferred target of the monarchist governments’ control measures. The new regime relied on conservative Catholicism and placed women in a situation of dependence and subordination to men. Nevertheless, in the republican movement many women took part in collective action: they participated in rallies and meetings, swelled the ranks of associative and cultural organizations and fought against the monarchy in various arenas. Their public presence led to greater visibility, their own forms of organization and the dissemination of discourses in defense of their rights, as well as a change in the gender culture in some republican groups.